2019
DOI: 10.3390/en12081459
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Inclined Magnetic Field on Carreau Nanoliquid Thin Film Flow and Heat Transfer with Graphene Nanoparticles

Abstract: The thermodynamics of a Carreau nanoliquid thin film embedded with graphene nanoparticles past a stretching sheet is studied in the presence of inclined magnetic field and non-uniform heat source/sink. Graphene is a new two-dimensional amphiphilic macromolecule which has great applications due to its electrical and mechanical properties. The basic constitutive equations of Carreau nanoliquid for velocity and temperature have been used. Similarity transformations are adopted to achieve the nonlinear coupled dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

8
2

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 30 publications
(32 reference statements)
0
45
0
Order By: Relevance
“…Maleque 27 investigated activation energy accompanying both type of reactions of heating absorbing and evolving in the movement and heating transportation for which numerical solution was obtained through RKF with the collaboration of other procedure along with NS iteration procedure. Since activation energy is related to heating and saturation transferring so the heating and saturation transferring studies may be consulted in the references [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] .…”
mentioning
confidence: 99%
“…Maleque 27 investigated activation energy accompanying both type of reactions of heating absorbing and evolving in the movement and heating transportation for which numerical solution was obtained through RKF with the collaboration of other procedure along with NS iteration procedure. Since activation energy is related to heating and saturation transferring so the heating and saturation transferring studies may be consulted in the references [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] .…”
mentioning
confidence: 99%
“…Entropy generation in nanofluid flow can be studied in Alharbi et al [39]. The studied of nanofluids are further extended to liquid film due to its abundant uses in various sciences [40][41][42][43][44][45][46][47][48]. Nanomaterial transportation over a wedge was scrutinized by Hassan et al [49].…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al [34] discussed the effect of strong applied magnetic field on thin film flow of second grade fluid with entropy generation past a stretching sheet. Khan et al [35] investigated the effect of inclined magnetic field on flow and heat transfer containing graphene nanoparticles past a stretching sheet. Khan et al [36] reported the mixed convection in gravity-driven non-Newtonian nanoliquid thin films (Casson and Williamson) flow containing both nanoparticles and gyrotactic microorganisms along a convectively heated vertical solid surface with the actively controlled nanofluid model boundary conditions to investigate the liquids thermodynamics analytically.…”
Section: Introductionmentioning
confidence: 99%